Thus Spoke the Posthuman: New Trajectories for the Study of Literature and Culture (KULT_online, 2020)
Reconfiguring Human, Nonhuman and Posthuman in Literature and Culture by Sanna Karkulehto, Aino-Kaisa Koistinen, and Essi Varis presents an array of theoretical and analytical approaches that encourage the reader to move beyond the traditional anthropocentric assumptions that still dominate literary and cultural studies. Five sections dedicated to different ways of understanding the nonhuman explore alternative models of the human/nonhuman relationship, while investigating contemporary cultural objects, including fiction, videogames, and experimental design.